2014
DOI: 10.1590/0004-2730000003492
|View full text |Cite
|
Sign up to set email alerts
|

Brown adipose tissue: what have we learned since its recent identification in human adults

Abstract: Brown adipose tissue, an essential organ for thermoregulation in small and hibernating mammals due to its mitochondrial uncoupling capacity, was until recently considered to be present in humans only in newborns. The identification of brown adipose tissue in adult humans since the development and use of positron emission tomography marked with 18-fluorodeoxyglucose (PET-FDG) has raised a series of doubts and questions about its real importance in our metabolism. In this review, we will discuss what we have lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 99 publications
(166 reference statements)
0
22
0
6
Order By: Relevance
“…Despite the very small sample size, the increase was observed in all patients, suggesting that melatonin may be a potential BAT recruiter that should be taken into consideration in further studies in humans, at least in situations in which a reduction in melatonin production occurs. Many experimental studies associated melatonin treatment with an increase in BAT mass as well as melatonin deficiency with a decrease in BAT mass, but these data were restricted to animal studies, mainly hibernating animals (3), and were obtained before the identification of active BAT in human adults (6)(7)(8). Today, BAT is being studied in view of its possible relation with obesity, type 2 diabetes, and other metabolic diseases, and potential BAT activators and recruiters have been proposed (20) as adjuvant treatment of these diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the very small sample size, the increase was observed in all patients, suggesting that melatonin may be a potential BAT recruiter that should be taken into consideration in further studies in humans, at least in situations in which a reduction in melatonin production occurs. Many experimental studies associated melatonin treatment with an increase in BAT mass as well as melatonin deficiency with a decrease in BAT mass, but these data were restricted to animal studies, mainly hibernating animals (3), and were obtained before the identification of active BAT in human adults (6)(7)(8). Today, BAT is being studied in view of its possible relation with obesity, type 2 diabetes, and other metabolic diseases, and potential BAT activators and recruiters have been proposed (20) as adjuvant treatment of these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, positron emission tomography (PET) with 2-deoxy-2-[fluorine-18] fluoro-D-glucose (FDG) showed that human adults present active BAT, especially after cold exposure (6,7). This finding quickly led to an exponential increase in BAT research, since activation of BAT leads to increased energy expenditure that could, at least theoretically, be a possible tool for the treatment of obesity and type 2 diabetes (8). Many compounds, including melatonin, have been studied to determine their ability of BAT recruitment and activation, although none of these studies have been carried out in humans (3,9).…”
mentioning
confidence: 99%
“…The effect of decreased lipid accumulation in canine adipocytes by encapsulated KO xenograft can have important implications for treatment of metabolic diseases, particularly obesity. Dogs and humans have high natal levels of thermogenic brown fat, which is gradually decreased in adulthood rendering them susceptible to obesity and insulin resistance . Obesity is considered to be a modern epidemic influencing 30% of world population .…”
Section: Discussionmentioning
confidence: 99%
“…These reviews have summarized the various approaches of imaging BAT and their shortcomings [11]. Other reviews have pointed to the value of diet-induced thermogenesis [12]. More recently, pharmacological strategies for BAT recruitment have been reported as a target of obesity and insulin sensitivity [13, 14].…”
Section: Introductionmentioning
confidence: 99%